The The effect of consumption of selected nutrients on the occurrence and course of depression - Krasowska, Dominika; Jastrzębska-Mierzyńska, Marta; Kwiatkowski, Michał; Hermanowicz, Adam (Journal of Education, Health and Sport, 2021)
Depression is a disease characterized by both mental and somatic disorders. The 21st century turned out to be the time when depression became a real health threat not only to individuals but also to entire societies. There are many theories pointing to the causes of depression, but these immediate causes are still not definitively clear. Equivalent importance of neuroanatomical and psycho-social factors is indicated. Among the theories considered so far, there are biological, hormonal, neurotransmitter-related, describing the malfunctions of the limbic system and hypothalamus, psychological theories. The studies conducted so far show that psychosocial factors play an extremely important role in the etiology of depression. Symptoms of depression are very complex and multifaceted, and may vary in severity. As a result of studies on the risk factors for depression, a relationship between the deficiency of individual nutrients and the manifestation of depressive disorders has been shown. The aim of the study is to present the influence of particular nutrients on the occurrence and course of depression. A properly balanced diet, both quantitatively and qualitatively, has a positive effect on reducing the risk of depression, as well as improving the condition of people who already suffer from it. Among the nutrients of particular importance are vitamin D, magnesium, folic acid, tryptophan, zinc, omega-3 fatty acids, cobalamin, and some probiotic microorganisms.